Application of Nano-drug Delivery Technology in Overcoming Drug Resistance in Lung Cancer - Yingchun LU; Chunyu WANG; Bin LIU (Chinese Journal of Lung Cancer)
Lung cancer is one of the most malignant tumor, representing a significant threat to human health. In China, its mortality rate is the highest among all malignant tumors. The occurrence of drug resistance has resulted in unfavourable prognosis for patients with lung cancer, and overcoming drug resistance is a significant challenge that needs to be addressed. Nano-drug delivery technology has been an important approach to overcome drug resistance in lung cancer. Targeting to the mechanisms of drug resistance, by enabling the combined delivery of drugs, increasing the efficiency of drug delivery and improving the targeting and safety of drugs, nano-drug delivery technology offers a novel approach to tackling drug resistance in lung cancer. This paper describes the current status of lung cancer treatment, mechanisms of drug resistance, strategies to overcome drug resistance, and the application of nanotechnology in the diagnosis and treatment of lung cancer. In addition, it summarizes the recent research progress on the application of nano-drug delivery technology to overcome drug resistance in lung cancer. Finally, the current prospects and challenges of nano-drug delivery technology are discussed.